Motivational Interviewing in Patients with Chronic Conditions - Alfarisi, Naufal Raihan; Lestari, Dwi; Sujianto, Untung (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nurse service in the world today requires supporting therapy to overcome complex problems including biologically, psychologically, socially, culturally and spiritually. In chronic patients there are many supporting implementation, one of which is motivational interviewing which explains motivational communication as a tool in minimizing the effects of problems that occur in chronic patients. Motivational interviewing can help more patient awareness and compliance leads to more careful responsibilities on treatment and health. Objectives: To determine the effect of motivational interviewing on chronic patients. Literature search using Data Based Sciencedirect, Scopus, Proquest, JStor, and Pubmed. The keywords used are